Intangible differences: Investment during the pandemic and the role of financial constraints - Peter Bauer; Clemens Domnick; Peter Harasztosi; Désirée Rückert; Christoph Weiss (European Investment Bank (EIB), 2024)
We use the European Investment Bank Investment Survey (EIBIS) data to analyse the impact of the COVID-19 crisis on firm-level investment in tangible and intangible assets. We find considerable heterogeneity regarding the extent of the reduction of investment in different asset groups - with R&D investment declining the least, and investment in training and in machinery and equipment the most. This can be partly explained by the different income-elasticity of investments. Our results also suggest that financial constraints deterred investment activity both before and after the outbreak of the COVID-19 shock. These financing constraints were binding not only for tangible investment, but also for intangibles such as R&D and training. We find evidence for a higher sensitivity of R&D investments to the COVID-19 shock compared to tangible investments. Strong policy support implemented during the pandemic contributed to alleviating part of the negative impact of COVID-19 by mitigating the increase in the number of financially constrained firms
Keywords: 330